Characteristics of Different Strategies in Problems Solving of Linear Pattern - Yayan Eryk Setiawan (International Journal on Emerging Mathematics Education, 2022)
Generalization is the core of mathematical activities that are important to be taught to students. One of the material generalizations that are emphasized at the level of junior high school in Indonesia is the generalization of linear patterns. One strategy that is often used by students in generalizing linear patterns is a different strategy. However, many students do not know the usefulness of the difference in making general formulas, so that they are trapped in a recursive relationship. This problem can be overcome by analyzing the results of student work that has succeeded in generalizing linear patterns using different strategies. For this reason, this study aims to get a description of the characteristics of the different strategies of students who have succeeded in generalizing linear patterns. The approach that fits this research is a case study approach to 6 grade VIII junior high school students who successfully solved the problem of generalizing linear patterns using a different strategy. The results showed that there were six characteristics of different strategies used to generalize linear patterns, namely: (1) using the difference to be substituted into the nth term formula of an arithmetic sequence, (2) using the difference to substitute into linear pattern formula, (3) using difference as a multiple, (4) using the difference as a jump number, (5) using the difference to be placed in a different column, and (6) using the difference to determine the formula for generalizing linear patterns directly.